MELACAK ARGUMENTASI PENGGUNAAN SEMIOTIKA DALAM MEMAHAMI HADIS NABI - Afwadzi, Benny (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
ne"> During this time, the study of semiotics of hadith looks has less of interesting in the study of discourse text. Most scholars who engaged in this study prefer to bring semiotics to read the signs mentioned in verses of the Koran. In fact, the hadith of the Prophet himself as second after Koran contains the actual signs also interesting to uncover by the semiotics. Through this paper, the author founds there are at least three arguments of using of semiotics in the understanding of the hadith, the fist, ‘semiotics’ turned out to have been used by classical scholars in understanding the hadith; second, the hadith is the language and the language is a sign; and third, as a development of the hadith study in the present era<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />